Field Resistance to Phakopsora pachyrhizi and Colletotrichum truncatum of Transgenic Soybean Expressing the NmDef02 Plant Defensin Gene - Soto, Natacha; Hernández, Yuniet; Delgado, Celia; Rosabal, Yamilka; Ortiz, Rodobaldo; Valencia, Laura; Borrás-Hidalgo, Orlando; Pujol, Merardo; Enríquez, Gil A. (Frontiers in Plant Science, 2020)
Fungal diseases lead to significant losses in soybean yields and a decline in seed quality; such is the case of the Asian soybean rust and anthracnose caused by Phakopsora pachyrhizi and Colletotrichum truncatum, respectively. Currently, the development of transgenic plants carrying antifungal defensins offers an alternative for plant protection against pathogens. This paper shows the production of transgenic soybean plants expressing the NmDef02 defensin gene using the biolistic delivery system, in an attempt to improve resistance against diseases and reduce the need for chemicals. Transgenic lines were assessed in field conditions under the natural infections of P. pachyrhizi and C. truncatum. The constitutive expression of the NmDef02 gene in transgenic soybean plants was shown to enhance resistance against these important plant pathogens. The quantification of the P. pachyrhizi biomass in infected soybean leaves revealed significant differences between transgenic lines and the non-transgenic control. In certain transgenic lines there was a strong reduction of fungal biomass revealing a less severe disease. Integration and expression of the transgenes were confirmed by PCR, Southern blot and qRT-PCR; where the Def1 line, showed a higher relative expression of defensin. It was also found that the expression of the NmDef02 defensin gene in plants of the Def1 line did not have a negative effect on the nodulation induced by Bradyrhizobium japonicum. These results indicate that transgenic soybean plants expressing the NmDef02 defensin gene have a substantially enhanced resistance to economically important diseases, providing a sound environmental approach for decreasing yield losses, and lowering the burden of chemicals in agriculture.